PELATIHAN MANAGEMEN KEUANGAN BAGI MITRA BINAAN BAZNAS MICROFINANCE DESA (BMD) GUNUNGSARI TAHUN 2024: Financial Management Training For Gunungsari Village Baznas Microfinance (BMD) Partners Year 2024 - M. Zainuddin; Karmana, I Wayan; ., Nofisulastri; Zulaifi, Reza; Mustakim, Ichwanul; Gunawan, I Made Sony; Samsuri, Taufik; Hariadi, Ahmad; Yani, Ahmad (Al-Amal: Jurnal Pengabdian Masyarakat, 2024)
The obstacle to the assistance provided is that MSME actors still do not have awareness and understanding in managing the financial management of business results, which means that the business they run is not able to develop optimally. Seeing conditions like this, in this community service, we raised the title "Financial Management Training for MSME partners assisted by Baznas Microfinance Village (BMD) Gunungsari in 2024". This aims to ensure that MSME actors, especially those assisted by Baznas Microfinance Village (BMD) Gunungsari, can understand how to manage, record and develop the financial results of businesses that are being carried out in the hope that they can develop optimally. The data analysis used is an inductive analysis technique, namely data processing that starts with specific problems and then general conclusions are drawn. The sample for this activity consisted of 15 people spread across several different Baznas partner groups. The results of the training showed that participants were able to apply four financial report recording skills, namely profit and loss reports, financial flow reports, capital changes reports and balance sheets. This is expected to be able to increase the progress of MSME businesses assisted by Baznas Microfinance Village (BMD) Gunungsari